Prevalence of Rifampicin Resistant Tuberculosis and its Associated factors among Patients at Lubaga Hospital. - Nakiboneka, Winnie (Student's Journal of Health Research Africa, 2021)
Background: Tuberculosis (TB) remains one of the world's leading causes of adult morbidity and mortality resulting in an estimated 8.8 million incident cases and 1.4 million deaths Up to 92% of the TB cases occur in low and middle-income countries with the sub-Saharan Africa region hosting nine of the highest TB incidence countries globally Uganda is ranked 16th among the 22 high burden countries. It is estimated that nearly 60,000 MDR- TB cases occur annually in the sub-Saharan region and these comprise 14% of the global burden of TB. In Uganda West Nile, the general prevalence of Mycobacterium tuberculosis is reported to be 20.2% and MDR-TB is 2.7% Methodology: A cross-sectional descriptive study about the prevalence of rifampicin-resistant tuberculosis and its associated factors among patients was conducted on 384 TB patients at Lubaga hospital. The patients were selected by simple random sampling and data was collected by the use of a structured questionnaire and analysis were done using SPSS version 17. Results: The prevalence of rifampicin resistance according to this study's findings was 10%. The predisposing factors to rifampicin resistance were cigarette smoking (P-Value = 0.001), history of prolonged stay with a TB infected patient, (P-Value = 0.001), and history of a previously treated episode of TB among the study respondents (P-Value = 0.001). Conclusion and recommendations The government of Uganda needs to carry out more intensified mass sensitization of people about the dangers of cigarette smoking, particularly to HIV infected individuals. In the same line of sensitization, people need to be continuously reminded by the ministry of health about the signs and symptoms of TB so that community members can identify suspects and refer them for specialized diagnosis and management such that delayed detection of the disease is minimized which will also reduce on rifampicin resistance.